Analysis Of The Health Level Of State-Owned Banks Using The Camels Method Registeredon The Idx For The 2020-2022 Period - Sara Melati Octania Br Lumbanraja; Junawan; Dito Aditia Darma Nst (Yayasan Multidimensi Kreatif, 2024)
This study aims to test and analyze the soundness level of state-owned banks using the methods of Capital, Assets, Management, Earning and Liduidity and Sensitivity to market risk (sensitivity to market risk) listed on the Indonesia Stock Exchange 2018-2019 period. This type of research is descriptive qualitative. The research population of state-owned banks listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling method is a census. The results showed that the Health Level of Bank Negara Indonesia (Persero), Tbk, the Health Level of Bank Rakyat Indonesia (Persero), Tbk, Bank Mandiri (Persero), Tbk, Bank Tabungan Negara (Persero), Tbk were calculated using the CAMELS method as a whole. predicate Healthy.